Penric's labors - Bujold, Lois McMaster (Bujold, Lois McMaster. World of the five gods., 2022)
"Penric and Desdemona are back in three novellas from Grand Master Lois McMaster Bujold. Masquerade in Lodi: Bastard's Eve is a night of celebration for most residents in the canal city of Lodi-but not for sorcerer Learned Penric and his Temple demon Desdemona, who find themselves caught up in the affairs of a shiplost madman, a dangerous ascendant demon, and a very unexpected saint of the fifth god. The Orphans of Raspay: When the ship in which they are traveling is captured by Carpagamon island raiders, Temple sorcerer Penric and his resident demon Desdemona find their life complicated by two young orphans, Lencia and Seuka Corva, who are far from home and searching for their missing father. Pen and Des will need all their combined talents of mind and magic to unravel the mysteries of the sisters and escape from the pirate stronghold. The Physicians of Vilnoc: When a mysterious plague breaks out in the army fort guarding Vilnoc, the port capital of the duchy of Orbas, Temple sorcerer Penric and his demon Desdemona are called upon by General Arisaydia to resurrect Penric's medical skills and solve its lethal riddle. In the grueling days that follow, Pen will find that even his magic is not enough to meet the challenges without help from dedicated new colleagues-and the god of mischance. Includes a new introduction, "outroduction," and suggested reading order by Lois McMaster Bujold"--